Rekonstruksi Hukum Waá¸`Ä«: Pembaharuan Usul Fikih dan Respon terhadap Kajian Fikih - Siregar, Ahmad Sholihin (Fakultas Syariah IAIN Purwokerto, 2018)
This study aims to reconstruct the waá¸â€™Ä« law in uá¹£Å«l fiqh. This reconstruction is important considering the facts: mubá¹il which is always cited in fiqh, has no referrence to uá¹£Å«l fiqh, the ambiguity of waá¸â€™Ä«â€™s definition and its unsystematic function as explained in uá¹£Å«l fiqh. The reconstruction of waá¸â€™Ä« law in this article consisted of: 1) adding mubá¹il to waá¸â€™Ä« law. Mubá¹il, as a decree of Allah (khiá¹ÄbullÄh) which stipulates something as the cause of the cancellation of acts, is required in law because it is needed in explaining the law of acts, it is not the opposite of conditions (syará¹), and the decree (khiá¹Äb) about mubá¹il is found in the Qurâ€™an; 2) â€˜azÄ«mah should also be determened as khiá¹ÄbullÄh, which stipulates something as a special reason for the enactment of general law from special law, in addition to the initial definition. 3) the waá¸â€™Ä« law should be defined implicitly and exclusively as khiá¹ÄbullÄh, assigned something as determinant factor or measurement for mukallafâ€™s (legal subjects) deeds. 4) Restructuring of waá¸â€™Ä« law according to its function, i.e. by measuring taklÄ«fÄ« law, it must be divided into three parts systematically, namely: pre-acts (sabab-mÄni`-rukhá¹£ah-â€™azÄ«mah), in acts (syará¹-mubá¹il), and post-acts (á¹£ahÌ£Ä«hÌ£-bÄá¹il).